The Influence of Family Income Level on the Future Major Selection Approaches of Chinese Ordinary High School Students and the Potential Solutions - Yuchen Gu (Studies in Social Science & Humanities, 2023)
Education is an essential cornerstone of national rejuvenation and social progress, and the lifeblood of national development. The optimal allocation of educational resources is crucial. Due to the particularity of China’s college entrance examination system (Gaokao system), students must define their major at the age of 16. However, due to the differences in family income levels, there are numerous unscientific decision-making phenomena, including but not limited to cognitive bias and self-interest dilemma. The theory of information asymmetry is the main reason for the above problems. Therefore, establishing and improving the planning guidance mechanism of major selection for senior high school students is an effective way to reform and break through the above difficulties.